Exogenous Oxidative Stress in Human Spermatozoa Induces Opening of the Mitochondrial Permeability Transition Pore: Effect on Mitochondrial Function, Sperm Motility and Induction of Cell Death - Anita Bravo; Raúl Sánchez; Fabiola Zambrano; Pamela Uribe (MDPI AG, 2024)
Oxidative stress (OS) and disrupted antioxidant defense mechanisms play a pivotal role in the etiology of male infertility. The alterations in reactive oxygen species (ROS) production and calcium (Ca2+) homeostasis are the main activators for the mitochondrial permeability transition pore (mPTP) opening. The mPTP opening is one of the main mechanisms involved in mitochondrial dysfunction in spermatozoa. This alteration in mitochondrial function adversely affects energy supply, sperm motility, and fertilizing capacity and contributes to the development of male infertility. In human spermatozoa, the mPTP opening has been associated with ionomycin-induced endogenous oxidative stress and peroxynitrite-induced nitrosative stress; however, the effect of exogenous oxidative stress on mPTP opening in sperm has not been evaluated. The aim of this study was to determine the effect of exogenous oxidative stress induced by hydrogen peroxide (H2O2) on mPTP opening, mitochondrial function, motility, and cell death markers in human spermatozoa. Human spermatozoa were incubated with 3 mmol/L of H2O2 for 60 min, and intracellular Ca2+ concentration, mPTP opening, mitochondrial membrane potential (ΔΨm), ATP levels, mitochondrial reactive oxygen species (mROS) production, phosphatidylserine (PS) externalization, DNA fragmentation, viability, and sperm motility were evaluated. H2O2-induced exogenous oxidative stress caused increased intracellular Ca2+, leading to subsequent mPTP opening and alteration of mitochondrial function, characterized by ΔΨm dissipation, decreased ATP levels, increased mROS production, and the subsequent alteration of sperm motility. Furthermore, H2O2-induced opening of mPTP was associated with the expression of apoptotic cell death markers including PS externalization and DNA fragmentation. These results highlight the role of exogenous oxidative stress in causing mitochondrial dysfunction, deterioration of sperm motility, and an increase in apoptotic cell death markers, including PS externalization and DNA fragmentation, through the mPTP opening. This study yielded new knowledge regarding the effects of this type of stress on mitochondrial function and specifically on mPTP opening, factors that can contribute to the development of male infertility, considering that the role of mPTP in mitochondrial dysfunction in human sperm is not completely elucidated. Therefore, these findings are relevant to understanding male infertility and may provide an in vitro model for further research aimed at improving human sperm quality.